2005
DOI: 10.1002/crat.200410434
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of orientation relationships by EBSD and EDS on the example of the Watson iron meteorite

Abstract: The suitability of the electron back-scatter diffraction technique (supported by EDS) in order to study the complex microstructures of iron meteorites is demonstrated on the example of the Watson meteorite. The orientation relationships between the main phases kamacite, taenite and schreibersite/rhabdite as well as effects of the real structure have been investigated. In kamacite bands highly deformed blocks appear which show a contineous change of orientation. Plessitic regions are surrounded by deformed taen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
(40 reference statements)
2
17
0
Order By: Relevance
“…EBSD is the fastest and most reliable method for revealing the crystalline structure and orientation of a single-or multi-phase crystalline solid [18,19]. In addition, EBSD offers high spatial resolution and thus direct visualization of even nano-crystalline grain/domain structures.…”
Section: Resultsmentioning
confidence: 99%
“…EBSD is the fastest and most reliable method for revealing the crystalline structure and orientation of a single-or multi-phase crystalline solid [18,19]. In addition, EBSD offers high spatial resolution and thus direct visualization of even nano-crystalline grain/domain structures.…”
Section: Resultsmentioning
confidence: 99%
“…1 obtained on a 9% Cr steel. Similar features appear in many fcc-bcc martensitic materials such as CuZn brasses [3], bainitic steels [4] and FeNi meteorites [5][6][7]. They are not artefacts that could be attributed to the EBSD method, as Bunge et al also observed them by synchrotron X-ray diffraction [8].…”
Section: Introductionmentioning
confidence: 80%
“…Kurdjumow-Sachs [9] The determination of the OR can be realized either by filtering the PFs [5,6] or by more complex calculations [4]. Most of the time, the singular features around the averaged OR are simulated by a superposition of NW and KS ORs [13,14] or by a higher number of discrete ORs including NW, KS, GT and other intermediate ORs [7].…”
Section: Introductionmentioning
confidence: 99%
“…If the deformation of the surrounding meteoritic metal is too strong the determination of the OR is problematic or impossible (cf., for the Watson meteorite in [32]). …”
Section: Occurence Of the Phosphidesmentioning
confidence: 97%